2017
DOI: 10.1038/cgt.2017.9
|View full text |Cite
|
Sign up to set email alerts
|

The most prevalent side effects of pegylated liposomal doxorubicin monotherapy in women with metastatic breast cancer: a systematic review of clinical trials

Abstract: Despite benefits of systemic chemotherapy in breast cancer treatment, several patients with early-stage breast cancer will develop metastatic breast cancer (MBC). Doxorubicin is among the most active agents against MBC. However, the use of doxorubicin is related to some life-threatening side effects including cardiotoxicity. Many efforts were made to lessen the side effects of doxorubicin and improve its efficacy. Pegylated liposomal doxorubicin (PLD) is a product claimed to achieve these two objectives becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 18 publications
0
54
0
2
Order By: Relevance
“…They interact with DNA base pairs and inhibit macromolecular biosynthesis; likewise, they are related with topoisomerase II after it has broken the DNA chain, stopping DNA replication. Their most important side effect is cardiotoxicity, which considerably hinders the scope of their use [86]. There are many studies that have evaluated the efficacy of antracyclines, but the most recent is a PELICAN trial: a phase III study that noticed that both doxorrubicin and capecitabine are effective as first line therapy for metastatic BC [87].…”
Section: Main Textmentioning
confidence: 99%
“…They interact with DNA base pairs and inhibit macromolecular biosynthesis; likewise, they are related with topoisomerase II after it has broken the DNA chain, stopping DNA replication. Their most important side effect is cardiotoxicity, which considerably hinders the scope of their use [86]. There are many studies that have evaluated the efficacy of antracyclines, but the most recent is a PELICAN trial: a phase III study that noticed that both doxorrubicin and capecitabine are effective as first line therapy for metastatic BC [87].…”
Section: Main Textmentioning
confidence: 99%
“…Therefore, patients on DOX chemotherapy are monitored regularly to assess cardiac LVEF and chemotherapy cessation is recommended when values drop below 40% [14]. PEGylated liposomal formulations of DOX can reduce the incidence of cardiotoxicity, though they have been associated with other side effects such as skin toxicity [15]. Currently, there are no cardiotoxicity-specific treatments, neither prophylactic nor curative, and cardioprotective drugs trialled in patients to treat DOX cardiotoxicity are sparse and include standard heart failure medications such as renin angiotensin system blockers and beta blockers [12,16].…”
Section: Introductionmentioning
confidence: 99%
“… 19 Doxorubicin is commonly used as part of the treatment regime for both early stage and metastatic breast cancer, but has severe toxicity issues. 20 Local drug delivery strategies represent a way to enhance the effectiveness of the drug, whilst reducing its side effects, by releasing a high concentration of the drug focally to the tumor. Local drug delivery is already in use for a range of malignancies, and drug delivery devices in development take on a range of different forms including wafers, films, nanoparticles, gels and rods (reviewed elsewhere 21 ).…”
mentioning
confidence: 99%
“…We speculate that this could be due to cardiotoxicity, a well-known side effect of doxorubicin therapy. 20 , 35 Assessment of tumor weight at the end of the study showed that i.v. doxorubicin dosing reduced the average tumor mass from 549 mg ± 326 ( i.e.…”
mentioning
confidence: 99%